EVALUASI PENGGUNAAN APLIKASI IPASERTUNTAS SEBAGAI SUMBER BELAJAR SEJARAH DI KELAS XI SMAN 1 MUARA KOMAM KABUPATEN PASER KALIMANTAN TIMUR - Fadilatul Khotimah, Octaviona; Rochgiyanti; Prawitasari, Melisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the evaluation of the iPaserTUNTAS application as a history learning resource for eleventh-grade students at SMAN 1 Muara Komam, Paser Regency, East Kalimantan. SMAN 1 Muara Komam has limited history learning resource books and access to the nearest regional library is relatively far. To overcome this challenge, the Paser Regency Archives and Library Service introduced the iPaserTUNTAS digital library application as an alternative learning resource. This study aims to evaluate the use of the iPaserTUNTAS application as a history learning resource for eleventh-grade students from the perspectives of students, history teachers, and the Archives and Library Service. This study used a qualitative method with a case study approach. Data were collected through classroom observations, semi-structured interviews, and document analysis. Informants were selected using purposive sampling. Data validity was ensured through triangulation of sources, techniques, and time, while data analysis followed the interactive model of Miles and Huberman. The findings indicate that iPaserTUNTAS plays an important role in expanding students' access to digital history resources, encouraging reading habits, supporting independent learning, and increasing flexibility in accessing educational materials both inside and outside the classroom. This application also contributed to increased student engagement and participation during history learning. However, several challenges were identified, including login difficulties, limited digital book copies, system errors, and a heavy reliance on internet connectivity. In conclusion, iPaserTUNTAS has demonstrated significant potential as a digital learning resource for history learning. However, ongoing evaluation, system optimization, collection expansion, and infrastructure improvements are needed to improve its usability, accessibility, and long-term sustainability in supporting history learning.